INITIATION AND SLOW PROPAGATION OF A CRACK ALONG THE PLANE OF SYMMETRY OF A 3-D VISCOELASTIC TRANSVERSELY ISOTROPIC PLATE - Selivanov, M.F.; Fernati, P.V. (Reports of the National Academy of Sciences of Ukraine, 2023)
This paper investigates the initiation and quasi-static propagation of a through mode I edge crack in a three- dimensional plate, considering the hereditary properties of the material. The crack growth is modeled using the incrementalization of constitutive equations and the criterion of critical opening displacement. The algorithm tested for solving the corresponding planar problem is applied to the plane of symmetry of the plate. The incubation time is calculated by successively determining the time it takes for the opening at the crack tip on the plane of symmetry to reach the critical opening fraction. The changes in opening over time are illustrated for both the plane of symmetry and the outer plane of the plate.